1998
DOI: 10.1007/s002689900405
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Resection in the Elderly

Abstract: From 1986 to 1995 a total of 97 patients > 65 years of age underwent hepatic resections at the Department of General Surgery, Hospital Lainz, Vienna, Austria. The population consisted of 39 men and 58 women with a mean age of 74.0 +/- 5.5 years. Primary neoplasia of the liver was the cause of resection in 35 patients, gallbladder cancer in 16 patients, and metastatic disease to the liver (due to colorectal cancer in 70%) in 40 patients. The rate of major resections (> or = 3 liver segments) was 96% for primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 36 publications
3
40
1
2
Order By: Relevance
“…The mortality rate of 6.6% is in accordance with published data of comparable cohorts of patients. Overall, both frequency and pattern of morbidity and mortality in the present study thus resemble that of hepatic resection surgery in general [19,20].…”
Section: Discussionsupporting
confidence: 50%
“…The mortality rate of 6.6% is in accordance with published data of comparable cohorts of patients. Overall, both frequency and pattern of morbidity and mortality in the present study thus resemble that of hepatic resection surgery in general [19,20].…”
Section: Discussionsupporting
confidence: 50%
“…The influence of age on the outcome of surgery has already been extensively analyzed in some fields, that is, cardiovascular surgery, which for epidemiological reasons are more frequently involved in the treatment of the elderly [15,16], while studies evaluating how age affects the onset of complications after hepatic resections are still infrequent in the literature. Some authors [1] have reported that in patients older than sixty-five, the mortality rate following hepatic resections is 11.1% compared to 3.6% in young patients and a subsequent study [4], by analyzing a population of elderly patients subjected to major hepatic resections to evaluate the outcome of aggressive surgical approaches, has shown a further and significant increase of the mortality in elderly patients compared to young patients (30% vs. 13%).…”
Section: Discussionmentioning
confidence: 97%
“…Hepatic resection is presently the treatment of choice for a wide range of primary and secondary liver diseases [1][2][3][4]. Major liver resections have recorded an impressive reduction in mortality over the last few years, going from 20% in the Seventies to the current less than 5% [5].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Furthermore, elderly patients have signifi cantly higher postoperative pulmonary complication-associated mortality than younger patients. 13 Therefore, it is essential to establish a preventive strategy against pulmonary complication in this patient population.…”
Section: Discussionmentioning
confidence: 99%